« La lutte des sexes », ou les stéréotypes sur les femmes dans Une vie secrète de Lenormand, La Valse des toréadors d’Anouilh et Capitaine Bada de Vauthier - Kaczmarek, Tomasz (Romanica Silesiana, 2021)
August Strindberg is considered the herald of modern drama. His protean work, which goes from naturalism to mystical aesthetics, anticipating surrealism and the theater of the absurd, even today defies, as it did in his epoch, by its brutal or cruel aspects. Without any doubt, the origin of a certain mistrust towards the author of Inferno would be his declared misogyny. It could be criticized on this subject for disclosing prejudices against women, which in the form of stereotypes, survive to this day. Nevertheless, many French playwrights are inspired by the infernal conflict between man and woman that the Swede describes with a stripping frenzy. Indeed, by analyzing the plays of the French theater of the first half of the 20th century, we notice that some authors take up the motive of the “struggle of the sexes” that will be reworked or “modernized” in their own way. It is interesting in this regard to study the vehicular discourse of clichés on women, found in the works of writers such as Henri-René Lenormand (A Secret Life), Jean Anouilh (Waltz of the Toreadors) and Jean Vauthier (Captain Bada). While none of these playwrights has ever openly declared their hostility to the so-called weaker sex, their texts provide a valuable reservoir of common ground on male-female relationships, which in most cases have not lost their actuality.